STRENGTHENING HUMAN NETWORKS IN THE ECONOMIC FIELD THROUGH ISLAMIC STUDY TOWARDSA ADVANCED COMMUNITY POST-COVID PANDEMIC - Ade Khadijatul Z. Hrp; Rahmat Rahmat (Proceeding International Seminar of Islamic Studies, 2022)
This study examines the Human Network in the Economic Sector through Islamic Studies Towards an Advanced Society after the Covid 19 Pandemic which is influenced by several factors, namely new opportunities, spending savings, acceleration of Islamic economic recovery, work system patterns, short courses training programs, education, entrepreneurship. . This study aims to provide an overview and analyze how to approach Islamic economic studies in answering economic problems due to the COVID-19 pandemic towards a developed society. This research is a descriptive research with a qualitative approach. The findings from this study reveal that every family will save on spending, the model of the work system in the future will change, holding entrepreneurial training programs such as culinary and others and culinary will certainly not be lonely, of course according to the choice of culinary type, families must be able to produce education with graduates independent and contribute to society and families must be able to answer the needs and challenges of competency-based learning methods, entrepreneurship can also be entrepreneurship soft skills. The conclusion in this study is the development of entrepreneurial competence using the coaching method. And to address real-world challenges using the business partnership model. Keywords: Economics, Islamic Studies, Advanced Society, Covid 19.